Union wage setting and international trade - Hartmut Egger; Daniel Etzel (University of Trier, Institute for Labour Law and Industrial Relations in the European Union (IAAEU), 2012)
This paper sets up a general oligopolistic equilibrium model with two countries that differ in the centralization of union wage setting. Being interested in the consequences of openness, we show that, in the short-run, trade increases welfare and employment in both locations, and it raises income of capital owners as well as workers. In the long run, capital out ows from the country with the more centralized wage setting generate winners and losers and make the two countries more dissimilar in terms of unemployment of welfare. Decentralization of wage setting can successfully prevent capital out ow and the export of jobs.
Keywords: F12; F16; J51; L13; 330; General oligopolistic equilibrium; Union wage setting; Asymmetric labor market institutions; Trade liberalization; Capital mobility; Decentralization in union wage setting; Lohnbildung; Lohnpolitik; Tariflohn; Tarifpolitik; Handelsliberalisierung; Kapitalmobilität; Oligopol; Mehr-Länder-Modell; Theorie